Second-language proficiency modulates the brain language control network in bilingual translators: an event-related fMRI study. Issue 2 (20th March 2020) - Mouthon, Michael; Khateb, Asaid; Lazeyras, François; Pegna, Alan J.; Lee-Jahnke, Hannelore; Lehr, Caroline; Annoni, Jean-Marie
Abstract: In bilinguals, language proficiency has been advanced to influence the involvement of domain-general control networks in language selection. We assessed, in university student translators with moderate- to high-second language (L2) proficiency depending on their translation educational level, the functional activity in the key language and control areas (the caudate nucleus, anterior cingulate, and prefrontal cortex), during task- and language-selection in an oral production context. We found that L2 proficiency influenced the relative involvement of our regions of interest during language selection vs domain-general cognitive control processes. While the left middle frontal and left caudate areas were more involved during linguistic than alphanumeric task selection in the low L2 proficiency group, these regions were similarly involved in both tasks in the high-L2 proficiency group. These findings suggest that language selection relies primarily on a network within domain-general cognitive control system with an increase in resource needs when L2 proficiency is low.